Applying Conversation Analysis
XX, 292 p. 3 illus.
Keywords: This book explores the relationship between conversation analysis and applied linguistics, demonstrating how the analysis of institutional talk can contribute to professional practice. With a foreword by Paul Drew, the core of the collection deals with topics as diverse as speech therapy and retailing; radio journalism and cross-cultural training.